Development of Trees outside Forests Resources in India – Need for Enabling Regulatory Framework - Bansal, Arun Kumar (Indian Journal of Agroforestry, 2026)
The primary aim of India’s National Forest Policy, 1988 is to ensure environmental stability and maintenance of ecological balance. This brought in a paradigm shift in forest management towards conservation, ecological stability, and ecosystem services. The policy envisaged forest-based industries raising the raw material needed for meeting their requirements, preferably through direct relationships between industries and farmers, while encouraging cultivation of tree species required by industries. This resulted in enhanced focus on Trees Outside Forests (ToF), including agroforestry, to meet the growing demand for wood and wood products.The prevalent regulatory framework is often cited as a hurdle in the growth of tree cultivation on private lands. However, liberal or no transit regulation on tree species grown on non-forest areas or preferred by farmers is only a necessary, not a sufficient, condition for the expansion of ToF and agroforestry. Efficient downstream processing using appropriate technologies, infrastructure development, and awareness regarding the use of wood and wood substitutes from plantation timber and renewable fibres are equally important.A multi-stakeholder committee constituted by the Ministry of Environment and Forests in July 2011, headed by the author, critically analysed state legislations and rules governing felling and transit of tree species grown on private/non-forest lands. The committee recommended relaxation of regulatory provisions for species preferred by farmers and agroforestry practitioners. Referring to this report, the National Agroforestry Policy, 2014 emphasized inclusion of these recommendations in its implementation guidelines and highlighted the need to address regulatory bottlenecks affecting agroforestry growth.This paper analyses the actions taken since the National Agroforestry Policy to liberalize regulations related to tree cultivation on private lands and suggests measures for creating an enabling legal framework for the development of ToF resources and agroforestry systems in India.